(untitled) (Journal of Technology Research, 2025)
Libyan cities are characterized by climatic conditions that vary between coastal, semi-desert and desert, which covers most of the Libyan state. The city of Bani Walid is located in the semi-desert region, where it is represented by high temperatures in summer, extreme cold in winter with a shortage of Water Resources and high rates of solar radiation. These climatic characteristics have played a key role in shaping the local urban environment, of which the housing sector constitutes the largest part, by following up the issued data showing that the highest rates of energy consumption in Libya in general and the city of Bani Walid in particular is consumed for cooling and heating.it has been noted that these rates have increased significantly in recent years, especially in modern detached housing. this study aims to analyze the impact of local building materials and building design on the thermal performance of detached housing in the semi-desert cities of Libya, focusing on the city of Bani Walid as a model for the study. The DesignBuilder program was used to simulate the thermal performance of the internal voids of the study samples according to the difference in the quality of building materials, the design style, and the analysis of their thermal performance rates. The results shown by the program show the effectiveness of each building in terms of thermal performance and the preparation of appropriate solutions to increase the efficiency of the study samples without the use of air conditioning and heating devices, thereby reducing the hours of energy consumption and thereby increasing the levels of sustainability in this type of buildings.